Development of a Mathematical Model and Solution to the Problem of Optimizing the Vacuum Block of Oil Distillation Unit - Safarova, A.A. (Herald of Azerbaijan Engineering Academy, 2024)
As it is known, one of the initial and important stages in the creation of optimal control systems of oil refining technological units is the development of a mathematical model that can adequately record the processes at any time. Studies have shown that the lack of information about the state of complex oil refining processes in many cases reduces their efficiency and effectiveness. On the other hand, the wide range of both quality and quantity of raw materials for processing makes their efficiency even more unsatisfactory. Under these conditions, it is difficult to develop mathematical models that can adequately describe the static modes of technological processes. Due to this the development of mathematical models is relevant both in scientific and practical terms. Taking into account the above, in the presented paper is developed a deterministic mathematical model that can adequately reflect the current technological operating conditions of a vacuum unit, which is the main device of the vacuum column of the primary oil refining technological complex. On the basis of this model, an optimization algorithm is developed that allows to calculate the optimal operating modes of the vacuum block.